2005
DOI: 10.1007/s00421-005-1322-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent short-term graded running performance in middle-distance runners in hypobaric hypoxia

Abstract: This study investigated whether in trained middle-distance runners, intermittent short-term graded running performance is affected by a hypobaric hypoxic environment (simulated 2,500 m) (H). Seven male middle-distance runners performed an aerobic performance test and an intermittent short-term graded anaerobic running-performance test (MART) both in H and in a normobaric normoxic environment (N). VO(2max) and OBLA were markedly lower (by 18.1% and 8.7%, respectively) in H than in N. In MART, neither maximal ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
4
3
0
Order By: Relevance
“…This study agrees with our previous study (Ogawa et al 2005), where we also observed a similar running performance (V max and TRT) in both N and H. The subjects in the present study were runners of a similar level than the participants in our previous study (Ogawa et al 2005) and two of the subjects were from the previous study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study agrees with our previous study (Ogawa et al 2005), where we also observed a similar running performance (V max and TRT) in both N and H. The subjects in the present study were runners of a similar level than the participants in our previous study (Ogawa et al 2005) and two of the subjects were from the previous study.…”
Section: Discussionsupporting
confidence: 94%
“…Balsom et al (1994) reported in athletes, that intermittent sprint cycling (ten bouts of 6 s exercise with 30 s recovery) performance was lower in the ninth and tenth bouts at simulated altitude of 3,000 m above sea level than in normoxia. In agreement, Brosnan et al (2000) reported that intermittent cycling exercise performance (15 s intensive exercise with 15, 30, 45 s recovery) was impaired at the moderate altitude of 2,100 m. On the other hand, we reported previously that maximal performance during intermittent graded sprint running (20 s running with 100 s recovery) did not change at a simulated altitude of 2,500 m compared to sea level (Ogawa et al 2005). Several authors have provided evidence for an increased participation of anaerobic metabolism during sprint exercise at simulated altitude between 3,800 m (Weyand et al 1999) and 5,300 m (Calbet et al 2003;McLellan et al 1990).…”
Section: Introductionsupporting
confidence: 72%
“…In line with previous research (Smith and Billaut, 2010; Bowtell et al, 2013), we observed well-preserved quadriceps muscle activation and associated power output during the two 4-s maximal cycling bouts under HY and NM conditions, which has been attributed to an enhancement of the anaerobic energy supply during isolated, all-out exercise bouts in acute HY (Ogawa et al, 2005; Morales-Alamo et al, 2013). These results, together with a greater overall perceived peripheral discomfort and perceived difficulty breathing during the two maximal-effort cycling bouts, suggest that perceptions of peripheral discomfort may not be the major contributor to exercise regulation during brief maximal-effort cycling bouts.…”
Section: Discussionsupporting
confidence: 92%
“…As such, team-sport athletes may be able to improve their sprint performance if they are able to enhance their ability to deplete large amounts of high-energy phosphates at a fast rate (ie, their anaerobic capacity) 27. Anaerobic performance lasting 30 s or less on either a cycle ergometer (Wingate test28–30) or a non-motorised treadmill31 32 is generally not adversely affected at altitude due to enhanced anaerobic energy release (ie, higher oxygen deficit or muscular lactate concentration),28 30 to compensate for the reduced aerobic ATP production. A high rate of anaerobic energy release during exercise has been proposed to be an important stimulus to increase anaerobic capacity 33.…”
Section: Introductionmentioning
confidence: 99%